The garden asparagus (Asparagus officinalis L.) mitochondrial genome revealed rich sequence variation throughout whole sequencing data - Sheng, Wentao; Deng, Jianlan; Wang, Chao; Kuang, Quan (Frontiers in Plant Science, 2023)
Background: Asparagus officinalis L. (A. officinalis) is a horticultural plant with important nutritional and medical value. It is also considered as the ideal material for many sex studies of dioecious plants. The genome information is helpful for resolving genetics and breeding issues. Results: Herein, the entire mitochondria (mt) genome of A. officinalis was sequenced, annotated and assembled with a mixed Illumina and PacBio data. A. officinalis showed a circular mt genome structure in the size of 492,062 bp with 45.9% GC value. In total, 36 protein-coding genes, 17 tRNA and 6 rRNA genes were annotated, and 8 protein-coding genes included 16 introns. Moreover, 254 SSRs, 10 perfect tandem repeats, and 293 non-tandem repeats were marked out. It was found that the amino acids in the codons of the edited sites showed a leucine-formation trend, and RNA editing sites mainly caused the mutual transformation among amino acids of the same nature. Meanwhile, 72 sequence fragments with 20,240 bp were observed to migrate from the cp to mt genome of A. officinlais, accounting for 4.11% of the whole mt genome. The phylogenetic analysis showed that A. officinlais had the closest genetic relationship with Allium cepa at the family level. Data also demonstrated that the majority of protein-coding genes had evolutionary conservative attributes, among which their Ka/Ks value was less than 1. Conclusion: Taken together, the complete mt genome of A. officinalis was annotated and analyzed in this study comprehensively. These findings will improve our understanding of the nucleotide composition features and phylogenetic relationship of the mt genome in A. officinalis L., and supplied more molecular data for mt comparative genomics in the genus Asparagus.